Thermokinetic behavior of Ga-doped GeTe4 glasses - Svoboda, Roman; Brandová, Daniela; Chromcikova, Maria; Liska, Marek (Elsevier Science BV, 2019)
Differential scanning calorimetry (DSC) and thermomechanical analysis (TMA) were used in conjunction to study thermokinetic behavior of (GeTe4)(y)(GaTe3)(100-y) bulk infrared glasses (for y between 40 and 100). The DSC data were utilized to describe the glass transition and crystallization kinetics in terms of the Tool-Narayanaswamy-Moynihan and Sestak-Berggren models, respectively. The kinetic data are of sufficient quality to enable predictions utilizable for preparation of Ge-Ga-Te ceramics and glass-ceramics. Whereas the compositional evolution of the positions of glass transition and crystallization effects was found to be small, the activation energies obtained for the two processes have shown that in case of the crystallization process the applied heating rate q(+) has large influence on the position of the corresponding kinetic peak on the temperature axis (T-c) and, consequently, on the values of glass stability and glass-forming criteria calculated by using this value. For this reason, a new viscous-flow-related criterion, which utilizes the joint DSC and TMA measurements and is independent from applied q(+), was derived to consider the thermal stability of the glassy materials with regard to their processing (fiber-drawing or shape-molding). Based on the newly developed criteria, the (GeTe4)(67)(GaTe3)(33) glass (positioned near the eutectic) was found to be optimal with respect to the fiber-drawing procedure.
Termokinetické chování Ga-dopovaných GeTe4 skel
Keywords: Ge-Ga-Te glasses; Glass transition; Crystallization; Thermal stability; DSC; TMA; Ge-Ga-Te; skelný přechod; krystalizace; tepelná stabilita; DSC; TMA